ANALISIS POSTUR KERJA TERHADAP PRODUKTIVITAS PEKERJA DI PT X DENGAN PENDEKATAN ERGONOMI - Alika Fathona Namirahadi, (2021)
PT X is a company that provides stamping and manufacturing services. Activities in PT X are mostly done manually, for example in the packaging station, it still uses human power without help from machines. The packaging process if done with bad posture can cause risk if done continuously. The methods used in this research are Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA), Job Strain Index (JSI), and Nordic Body Map (NBM) to determine their effect on worker productivity. The RULA, REBA, and JSI results show that workers at the packaging station have a high level of risk with NBM results of 100% workers feel pain in the back and waist, 67% feel a bit pain in the upper neck. The proposed improvement is to design and implement tools according to anthropometry such as working chairs for packaging workers. The results of the comparison between RULA, REBA, and JSI before and after the implementation change showed that the worker's risk level decreased. The NBM results showed that 33% of workers felt a bit of pain in the upper neck and back, and 67% felt a bit of pain in the waist. Work productivity at the packaging station increased between 9%-12% which means that workload and work posture have an effect on worker productivity.